Challenges and prospects in geriatric epilepsy treatment: the role of the blood–brain barrier in pharmacotherapy and drug delivery - Chen, Xin; Luo, Juan; Song, Min; Pan, Liang; Qu, Zhichuang; Huang, Bo; Yu, Sixun; Shu, Haifeng (Frontiers in Aging Neuroscience, 2024)
The blood–brain barrier (BBB) is pivotal in maintaining neuronal physiology within the brain. This review delves into the alterations of the BBB specifically in the context of geriatric epilepsy. We examine how age-related changes in the BBB contribute to the pathogenesis of epilepsy in the elderly and present significant challenges in pharmacotherapy. Subsequently, we evaluate recent advancements in drug delivery methods targeting the BBB, as well as alternative approaches that could bypass the BBB’s restrictive nature. We particularly highlight the use of neurotropic viruses and various synthetic nanoparticles that have been investigated for delivering a range of antiepileptic drugs. Additionally, the advantage and limitation of these diverse delivery methods are discussed. Finally, we analyze the potential efficacy of different drug delivery approaches in the treatment of geriatric epilepsy, aiming to provide insights into more effective management of this condition in the elderly population.